Response Of Liquid Organic Fertilizer Eco Enzyme (EE) On Growth And Production Of Shallot (Allium Ascalonicum. L) - Novianto Novianto (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Shallots are horticultural products that have high economic value. For obtaining quality shallots, there is an optimal cultivation action. One way that can be done to increase productivity is through fertilization. Organic fertilizers derived from household waste such as vegetable and fruit waste can manufacture liquid organic fertilizers whose final results are called eco-enzymes (EE). Eco enzymes can provide nutrients and improve physical attributes, soil's chemical and biological properties, and product quality. The purpose of the study was to determine the response of the eco-enzyme liquid organic fertilizer application to shallot plant growth and production and determine the appropriate application dose for the growth and production of shallots. The method used in this study used a non-factorial randomized block design (RAK) method. The dose of EE LOF application consists of 6 levels, namely E1 = 0.5 ml/L water, E2 = 0.75 ml/L water, E3 = 1 ml/L water, E4 = 1.25 ml/L water, E5 = 1.5 ml/L water, E6 = 1.75 ml/L water. Analysis of the data used the mathematical model of Analysis of Variety Prints, and further tests were carried out using the Honestly Significant Difference Test (HSD) at 5% and 1% levels. The results showed a very significant effect on the parameters of root length and significantly affected the number of leaves at a dose of 1.75 ml/L of water.